163 Effects of pre- and post-partum supplementation of molasses/urea with or without methionine fortification on growth performance of primiparous cows and their offspring. (29th July 2019) - Vedovatto, Marcelo; Palmer, Elizabeth; Ranches, Juliana; Miranda, Miguel; Gouvêa, Vinícius; Arthington, John; Vendramini, João; Moriel, Philipe
Abstract: The present study evaluated the performance of calves born from primiparous cows offered pre- and post-partum supplementation of sugarcane molasses/urea added or not with DL-methionine hydroxyl analog. On d 0 (~56 d before calving), 36 Brangus heifers were stratified by BW and BCS (345 ± 4.7 kg; 2 yr of age), and randomly allocated into 1 of 12 bahiagrass pastures (3 heifers and 1.2 ha/pasture). Treatments were randomly assigned to pastures (4 pastures/ treatment) and consisted of no supplementation (NOSUP) or supplementation of molasses/urea (7.2 kg DM/heifer/ wk; 75% TDN, 20% CP; DM basis) with (MOL+) or without (MOL-) fortification with 105 g/heifer/wk of methionine (Alimet, Novus International Inc., Romance, AR) from d 0 until all heifers within each pasture calved. Total weekly amount of molasses/urea (and methionine for MOL+ heifers) was divided by 2 and offered on Tuesdays and Wednesdays. After all cows calved, all pairs were fed 12.7 kg/cow/wk of molasses/urea (DM basis) and grazed a single bahiagrass pasture until calf early-weaning (d 147). Calves received a soybean hull-based supplement at 3.5% of BW (DM basis) and ad libitum stargrass hay from d 154 to 201. Calving date and cow BCS on d 44 did not differ between MOL+ and MOL- (P ≥ 0.50), but both groups calved at greater BCS than NOSUP cows (P ≤ 0.008). However, cow BCS on d 147 and pregnancy percentage on d 288 did not differ among treatments (P ≥ 0.27). Calf birth BW did not differ among treatments (P ≥ 0.21), but ADG from birth to d 201 was greater for MOL+ and MOL- vs. NOSUP calves (P ≤ 0.05). Therefore, pre- and post-partum supplementation of sugarcane molasses/urea improved cow BCS at calving and calf postnatal growth compared with no supplementation. Supplemental methionine did not further enhance cow and calf growth performance